Gambaran Identitas Etnis Remaja Suku Jawa dan Sunda - Aqiila Fathurroja; Humaira Mumtazah; Rosiana Rosiana; Siti Barkah Miarti Pudoli; Fridayanti Fridayanti (Jurnal Psikologi Islam dan Budaya, 2018)
Ethnic identity is important in cultural inheritance. In border areas, there are often mixing of two different ethnic groups. The purpose of this study is to obtain an overview of the ethnic identity of Sundanese and Javanese adolescents in the border region. The subjects in this study were  two group of students from one High school in Ciamis, a border area between West Java and central Java.  They were members of the Javanese and Sundanese ethnic groups (N=60).  The instrument used is the Multigroup Ethnic Identity Measure (MEIM) scale developed by Phinney (1992). Result shows that the two ethnic groups have almost the same sense of ownership, but they are low in exploring their ethnicity.